2007
DOI: 10.1186/1476-9255-4-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of the purinergic P2X7 receptor in inflammation

Abstract: The inflammatory process, orchestrated against a variety of injurious stimuli, is composed of three inter-related phases; initiation, propagation and resolution. Understanding the interplay between these three phases and harnessing the beneficial properties of inflammation whilst preventing its damaging effects, will undoubtedly lead to the advent of much needed therapies, particularly in chronic disease states. The P2X7 receptor (P2X7R) is increasingly recognised as an important cell surface regulator of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
207
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(211 citation statements)
references
References 151 publications
(166 reference statements)
1
207
0
3
Order By: Relevance
“…Of the seven P2X subtypes, by far the strongest body of evidence for involvement in mediating neuroinflammation exists for P2X7 (Lister et al, 2007). Gene-linking and epidemiological studies have implicated P2X7 in a host of CNS diseases (Hansen et al, 2008;Ursu et al, 2014).…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the seven P2X subtypes, by far the strongest body of evidence for involvement in mediating neuroinflammation exists for P2X7 (Lister et al, 2007). Gene-linking and epidemiological studies have implicated P2X7 in a host of CNS diseases (Hansen et al, 2008;Ursu et al, 2014).…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
“…P2X7 receptor activation of the inflammasome in response to high extracellular concentrations of ATP seems to rely primarily on K þ efflux through the cell membrane (Bernier, 2012;Lister et al, 2007). P2X7 receptor activation leads to an increase in permeability to K þ , either directly through the P2X7 receptor pore, or through the opening of pannexin-1 hemichannels (Panx1).…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, disruption of cellular membrane caused by the high plasma glucose and FFAs [18] can contribute to the accumulation of extracellular ATP [19]. Evidence has indicated that the P2X7 receptor was involved in the process of inflammatory response and release of inflammatory mediators [20,21]. Our previous studies also showed that the P2X7 receptor played a major role in the transmission of inflammatory signals and contributed to the pathological process of sympathetic injury [6,10,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 96%
“…In blood, the ATP released by healthy cells in response to stimuli such as shear stress and cell swelling, by damaged cells, by vascular injury or by stimulated platelets, [14,34] is able to stimulate several leukocyte functions such as DNA synthesis, blastogenesis, cell-mediated killing, apoptosis, pro-inflammatory activities, adhesion to endothelial cells, shedding of CD62L and expression of Mac1 [2,28,37,40]. These effects are mediated by purinergic receptors that belong to the metabotropic (P2Y) and/or ionotropic (P2X 1 -P2X 7 ) type [6,25,33].…”
Section: Introductionmentioning
confidence: 99%